Profit efficiency of U.S. commercial banks: a decomposition (2013)
This paper presents new evidence regarding the relation between profit, revenue, and cost efficiencies of U.S. commercial banks. Building on the widely used nonstandard profit function (NSPF) approach, we show (i) why estimation of NSPF would be wrong and (ii) how revenue and cost efficiencies contribute to profit efficiency. Using data from U.S. comercial banks from 2001 to 2010, we find that losses due to profit inefficiency represents about 8.2% of banks’ equity of which 3.5% is due to revenue inefficiency and 4.7% to cost inefficiency. Cost efficiency weighs more than revenue efficiency in estimated profit efficiency. However, compared with cost inefficiency, revenue inefficiency affects more overall profitability